Răspunsuri

2014-04-24T00:57:22+03:00
F:(-2)= 2 * (-2) +1 = 5   A (-2 ;5 )       ;   f(0)=2*0+1= 1   B(0 ;1)       ;   f(1)=2*1+1 = 3  C(1;3)           ;      f(2)=2*2+1=5    D(2;5)           si acum le pui pe axa xOy                                           Y
                                                                                                                                            

Cel mai inteligent răspuns!
2014-04-24T01:04:16+03:00
F(-2)=-4+1=-3
f(-1)=-2+1=-1
f(0)=1
f(1)=2+1=3
f(2)=4+1=5